Habitat suitability assessment and ecological network construction for shorebirds in Hainan Island, China - Chenyao Li; Qianqian Shi; Zhengkai Zhang; Yanlong Zhang (Ecological Indicators)
As a typical tropical island, Hainan Island in China is an important stopover along the East Asian-Australasian Flyway (EAAF), providing critical habitat for various shorebirds. However, with the rapid development of urbanisation and industrialisation, habitat destruction and fragmentation pose a serious threat to the survival of shorebirds. In this study, observations of shorebirds in Hainan Province from 2010 to 2020 were categorized using order (Ciconiiformes, Charadriiformes, Pelecaniformes, Anseriformes, Gruiformes, and Lariformes) as the unit of analysis. Using the model, we predicted potential habitat distributions for these shorebirds groups by integrating occurrence data with environmental factors, and determined suitable habitat ranges through fuzzy comprehensive evaluation. On this basis, the evaluation results were utilised as ecological sources. Subsequently, the ecological resistance surface was constructed, and the Linkage Mapper software was employed to construct the shorebirds habitat network. Ultimately, 88 ecological corridors and 21 ecological pinch points were identified. Based on the results of shorebirds habitat suitability assessment, habitat network analysis, and pinch point identification, this study further proposes ecological conservation strategies for shorebirds on Hainan Island.